Management of Shisham Wilt (Fusarium solani f.sp. dalbergiae) - ., Dayaram; Kumar, M.; Sharma, S.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
The effect of fungicides (Bavistin, Blitox 50 and Indofil M-45) and bioagents (Trichoderma viride, Aspergillus flavus and A. niger) In vitro and In vivo were studied against shisham wilt caused by Fusarium solani f.sp. dalbergiae (Fsd). In vitro, Bavistin completely inhibited the Fsd growth at 100, 300 and 500 ppm, whereas Blitox 50 and Indofil M-45 were less effective at these concentrations. Among bioagents, Trichoderma viride was found most effective and inhibited the growth of test pathogen upto 85%. Under field condition Bavistin and Trichoderma viride were effective when wilt affected trees were drenched 14 times with Bavistin @ 0.1% and 106 spores/ml with Trichoderma viride 3 times. Maximum survival of 84% & 72% and 60% & 48% trees were observed by Bavistin and Trichoderma viride during 2002-03 and 2003-04, respectively.